Hypersonic Flight - Olsson, Niklas; Uday Rane, Pranav; Rajan Sourirajan, Rahul; Savio Swamy, Kevin (TMAL02 Expert Conference, 2020)
The main areas of focus within hypersonic flight were hypersonic propulsion and re-entry vehicles. Findings of the study states, self sustained hypersonic flight need an advanced engine that can function through all Mach regimes. Aerodynamic design of re-entry vehicles require a different approach compared to atmospheric hypersonic flight.